PENGEMBANGAN MULTIMEDIA PEMBELAJARAN SD PADA MATERI CUACA TEMA 5 KELAS III - Fitriana, Fitriana; Herni, Herni; Dwi Lestari, Yulita (Program Studi PGSD, Jurusan Ilmu Pendidikan, STKIP PGRI Bandar Lampung, 2020)
Multimedia plays an important role in making a process learning takes place effectively, interestingly, and efficiently. Therefore, As an effort to increase the effectiveness of learning, and overcome limited teaching aids and learning media such as multimedia, teachers are required to be creative to develop or create these media. Research purposes this is to create learning media that attract participants' learning interest students to learn the material